Detection of viable commensal bacteria in murine melanoma tumors by culturomics - Catherine M. Phelps; Jake H. Shapira; Colin R. Laughlin; Marlies Meisel (STAR Protocols, 2023)
Summary: Emerging evidence suggests the tumor microbiome at gut-distal sites can modulate tumor immunity and response to cancer immunotherapy. However, detection of commensal bacteria at gut-distal tumor sites is challenging given their low abundance. Here, we present a culturomics approach to facilitate recovery of phylogenetically diverse live commensal bacteria within gut-distal melanoma tumors. We describe steps for media preparation, tissue isolation, tissue homogenization, and host cell lysis. We then detail broth expansion culture followed by agar culture and single-colony 16S rRNA sequencing.For complete details on the use and execution of this protocol, please refer to Bender and McPherson et al. (2023).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.